Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1038/leu.2009.48
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 mutations are frequent in chronic myelomonocytic leukemia and mutations at the C-terminal region might predict acute myeloid leukemia transformation

Abstract: Runt-related transcription factor 1 (RUNX1) is essential for normal hematopoiesis. RUNX1 mutations have rarely been reported in chronic myelomonocytic leukemia (CMML). We examined RUNX1 mutations in 81 patients with CMML at initial diagnosis. Mutational analysis was performed on bone marrow samples by direct sequencing of all reverse transcription PCR products amplified with three primer pairs that cover the entire coding sequences of RUNX1b. Thirty-two RUNX1 mutations were detected in 30 patients (37%); 23 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 32 publications
3
117
2
1
Order By: Relevance
“…Similar to our results, two recent studies reported RUNX1 mutations in 9 of 30 (33%) and 30 of 81 (37%) CMML patients, respectively. 26,27 In accordance with these studies, we also detected the majority (60%) of RUNX1 mutations within the Nterminal RUNT domain, which is the most conserved region of RUNX family members and is directly involved in DNA binding and interactions with CBFb. 28 Kuo et al described a higher risk of AML progression in CMML patients with RUNX1 mutations at the C-terminal compared to the N-terminal region.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to our results, two recent studies reported RUNX1 mutations in 9 of 30 (33%) and 30 of 81 (37%) CMML patients, respectively. 26,27 In accordance with these studies, we also detected the majority (60%) of RUNX1 mutations within the Nterminal RUNT domain, which is the most conserved region of RUNX family members and is directly involved in DNA binding and interactions with CBFb. 28 Kuo et al described a higher risk of AML progression in CMML patients with RUNX1 mutations at the C-terminal compared to the N-terminal region.…”
Section: Discussionsupporting
confidence: 63%
“…28 Kuo et al described a higher risk of AML progression in CMML patients with RUNX1 mutations at the C-terminal compared to the N-terminal region. 27 Although we observed a similar trend in our cohort (data not shown), the number of patients with C-terminal RUNX1 mutations was small in our study (n=6) as well as in that by Kuo et al (n=9). Overall we saw no difference in outcome between RUNX1-mutated cases and those without transcription factor mutations.…”
Section: Discussionmentioning
confidence: 35%
“…RUNX1 and RAS alterations, which were found exclusively in 46% of proliferative but not in myelodysplastic variant of CMML, were not mutually exclusive. Kuo et al 22 recently reported missense, silent, nonsense and frameshift mutations of RUNX1 in a cohort of 81 CMML patients. Thirty-two different mutations were detected in 30 patients (37%) with 23 mutations located in the N-terminal and 9 in the C-terminal region.…”
Section: *Information On Who 2008 Criteria Is From Orazi Et Almentioning
confidence: 99%
“…8,9 Recently, several genes have been found mutated in myeloid malignancies, including CMML. [10][11][12][13] These discoveries were facilitated by single nucleotide polymorphism array (SNP-A) karyotyping, which enables detection of somatic regions of copy number neutral loss of heterozygosity (CN-LOH), also called uniparental disomy (UPD).…”
Section: Introductionmentioning
confidence: 99%